Resistant bacteria in the adenoid tissues of children with otitis media with effusion - Karlidag, T; Demirdag, K; Kaygusuz, I; Özden, M; Yalçin, S; Öztürk, L (Elsevier Sci Ireland Ltd, 2002)
Objective: To investigate the relationship between the resistant bacteria in the adenoid tissue and the middle ear effusion of children who underwent myringotomy and adenoidectomy with the diagnosis of otitis media with effusion (OME). Methods: This study was performed in the ENT Clinic, Firat University between January 2001 and June 2001. Forty-one subjects who were enrolled in the study were diagnosed as OME, their age ranged from I to I I years, and they underwent a myringotomy together with an adenoidectomy because of adenoid hyperthrophy. Bacteriological cultures were performed on the samples obtained from adenoid tissues and middle car fluids, in the bacteria that were cultured; the resistance to oxacilline sodium and beta-lactamase were investigated. The resistance of penicillin was confirmed by MIC test, The control group composed of individuals who did not have OME but who underwent adenotonsillectomy due to adenotonsillary hyperthrophy. Results: In the adenoid tissue cultures. Haemophilus influenzae, Streptococcus pneumoniae and Moraxella catarrhalis species were isolated from the 70% (29/41) of the study group and 40% (20,41) of the control group (P < 0.01). In the isolated bacteria, the resistance rates for oxacilline or beta-lactamase were found to be 48% (20/41) in the study group and 16% (4,25) in the control group (P < 0.05). We observed that bacterial growth in 29% (9/31) of the middle ear cultures of the study group and resistant bacteria were isolated in 77% (7/9) of them. The same pathogens which have grown in the middle ear cultures were also present in the adenoid tissue cultures. Conclusion: The isolation of resistant bacteria in most of the adenoid tissue samples of the children with OME. makes us to consider the possible role of these bacteria in the development of OME. (C) 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: otitis media with effusion; resistant bacteria; adenoid tissue